Pentingnya Penerapan Metode Pembelajaran Kooperatif Group Investigation untuk Meningkatkan Prestasi Belajar Siswa - Paulinus Kanisius Ndoa; Mawarni Gea; Nobertanidarmawati Giawa (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
The group investigation type cooperative learning method is a cooperative learning model that is based on group discussions and involves students in small groups, compiling material and creating a learning environment that allows students to be brave and appear confident in expressing ideas or opinions, enjoy collaborating, actively participating. , so that students get a meaningful learning experience. The group investigation type learning method encourages students to be actively involved in learning planning from the beginning to the end of the learning process. This research was carried out using a literature review approach, where the researcher tried to examine ideas about group investigation type cooperative learning methods from many references. It was found in the research that the application of the group investigation type cooperative learning method contributed to student learning achievement. This learning method succeeds in creating an active learning environment and helps students to work cooperatively in solving problems. Apart from that, this learning method can grow students' thinking abilities and provide opportunities to learn more meaningfully in a social context with their group friends. Because of this, according to researchers, the group investigation type cooperative learning method should be the teacher's choice in the learning process.